Europäische Lyrik seit der Antike. 14 Vorlesungen - Hillmann, Heinz; Hühn, Peter (Europäische Schneisen, 2005)
Since ancient Greek-Latin and Judeo-Christian antiquity and also in a constant return to these two traditions the people of Europe have created a great treasure trove of poems. These poems have expressed and shaped the eras of their history. While myth, epic and novel have told the great stories of the world and of the gods, peoples and heroes, the poem created the ego-telling voice at an early age and thus enabled her to make herself heard and accentuated in the great and small events of the time; to try out feelings, attitudes, values and thus to prepare new mentalities.This division of labour between poem and narrative is always kept in view in the lectures of this book, because they use the now developed approaches of narrative research, narratology, to discover the special possibilities of poetry. Thus, one can see more clearly what role poems and songs play in the subjectivization of religion and love since the Reformation, how they promote the liberation of the individual in the Enlightenment, how they promote a new religion of nature and art, how they stimulate the nationalism of the 19th century and how to adopt new attitudes in the process of modern civilization with daring experiments. The specialist disciplines have distributed this common treasure among themselves and thus almost lost sight of it. The public lecture, however, has made it visible to those involved, always using the example and in a language accessible to all, which has been preserved in this book.